Sutureless Abdominal Closure in twin gastroschisis - Clara Zhu; Matthew Moront; Douglas Katz; Jacqueline English; Dorothy Gould; Matthew Boelig (Elsevier, 2021)
Gastroschisis is the most common congenital abdominal wall defect and the incidence of gastroschisis is increasing globally. Twin gastroschisis remains an extremely rare phenomenon. We present a case of premature dizygotic twins with simple gastroschisis born at 33 weeks and 3 days gestation. Both twins underwent primary reduction and sutureless closure using the umbilical cord remnant. We describe our technique for sutureless closure and subsequent wound care management. Neither twin required general anesthesia, intubation, mechanical ventilation, or antibiotics as a direct result of their gastroschisis management, and both twins had swift progression to full oral feeds by day of life 25 and 29. They have both had good cosmetic results with small umbilical hernias. This case report highlights a rare twin pairing of a common congenital anomaly and underlines the benefits of the sutureless closure technique.